2020
DOI: 10.1186/s12910-020-00529-8
|View full text |Cite
|
Sign up to set email alerts
|

The obstacles to organ donation following brain death in Iran: a qualitative study

Abstract: Background: Organ donation following brain death has become an important way of supplying organs for transplantation in many countries. This practice is less common in Iran for different reasons. Therefore, this study aims to explore the obstacles to organ donation following brain death in Iran. Methods: This qualitative research was conducted following the conventional content analysis method. The study population consisted of individuals with a history of brain death among their blood relatives who refused t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Furthermore, it is necessary to point out the existence of patient and family barriers based on cultural and religious influences, which can condition the acceptance of the transplant. In Iran, Abbasi et al [35] showed how poor knowledge about brain death and organ transplantation from a dead body, cultural beliefs, religious beliefs, deficiencies of the requesting process, fears and concerns, and the inability to make a decision were important barriers to accepting organ donation by families and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is necessary to point out the existence of patient and family barriers based on cultural and religious influences, which can condition the acceptance of the transplant. In Iran, Abbasi et al [35] showed how poor knowledge about brain death and organ transplantation from a dead body, cultural beliefs, religious beliefs, deficiencies of the requesting process, fears and concerns, and the inability to make a decision were important barriers to accepting organ donation by families and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our participants were religious. However, the majority of Croatian population is Catholic and given that the Catholic Church has a positive attitude regarding organ donation, these reasons remain somewhat unclear [31].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors state that organ donation is a unique social activity where there is a direct impact of the health professionals on to a wide range of patients [49]. Therefore, it is important to increase awareness and knowledge on the topic, as well as to provide social and mental support to the included parties [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although part of society views organ donation as an act of solidarity and love (8) , there are negative beliefs around the subject, related to lack of knowledge about the process, which influence individuals in the decision to donate or not their and/or their relatives' organs and tissues (1,(9)(10) . In Brazil, Law No.…”
Section: Introductionmentioning
confidence: 99%
“…10.211/2001 (11) determines that, for organ donation, there must be a diagnosis of brain death and the informed consent of relatives up to the second degree. These family members often decline to donate due to many reasons, such as: not understanding the situation; religious beliefs; fear of mutilation and threat to the entirety of the body; organ trade; professional negligence; impossibility of knowing the recipient; fear of the reaction of other family members; or inappropriate interview (5,7,10,(12)(13) .…”
Section: Introductionmentioning
confidence: 99%